Anxiety, depression, and support needs of the mothers of children with cerebral palsy and determining their opinions: Mixed methods study (vol 78, pg e133, 2024) - Sarman, Abdullah; Tuncay, Suat; Budak, Yusuf; Demirpolat, Eyyup; Bulut, Irem (Elsevier Science Inc, 2025)
[Abstract Not Available]